The dependence of thermal processes in non-metallic heterogeneous materials on mechanical vibration loads - Tonkonogyi, Volodymyr; Holofieieva, Maryna; Levynskyi, Oleksandr; Klimov, Sergii; Dasic, Predrag (Видавництво Львівської політехніки, 2023)
One of the promising directions in the development of mechanical engineering is using of new non-metallic heterogeneous materials with high physical and mechanical properties. Such materials consist of two or more components (reinforcing filler and polymer matrix) and have specific physical and mechanical properties that are different from the properties of the constituent components. This is achieved by forming a complex developed structure. Reliable control methods play an important role in ensuring the quality of such structures. The paper considers an acoustic infrared thermometric method of control, which is based on the interaction of structural defects with acoustic waves. At the same time, thermal energy is generated at their boundaries, which is an indicator not only of the presence of cracks but also of their direction and development. a mathematical model has been developed that describes the transformation of the energy of mechanical vibrations into thermal energy, which occurs in non-metallic heterogeneous materials.
Keywords: non-metallic heterogeneous materials; acoustic infrared method of control; flaw detection; thermal energy; the energy of mechanical vibrations